Marbel Application Based Learning Media to Develop Analytical Skills in Children Aged 4-5 Years - Fitri, Elisa; Dewa Gede Firstia Wirabrata (Universitas Pendidikan Ganesha, 2023)
Lacking the necessary facilities and tools in schools, teachers sometimes only use one medium to teach. Teachers also experience difficulties introducing the media to students, considering that children still need to learn numbers and initial number symbols. This research aims to create learning media based on marble applications to develop analytical skills in group B children. The development model used in this research is the ADDIE development model. The data collection method uses questionnaires and assessment tools (assessment forms). Analysis techniques with quantitative and qualitative analysis. Based on the content validity test by two experts, the content validity value was 0.93, where this value is classified as very high validity. The Marble fun numbers game application is suitable for developing children's analytical skills. The results of the effectiveness trial showed that the average value of the analysis ability of the small group of children after learning to use marble fun numbers was 80.2%, and the large group's total score was 81%; this was classified as very good. It was concluded that the marble application-based learning media for developing analytical skills in group B children was highly valid. Hence, the marble application-based development media for developing analytical skills in group B children was suitable.